2020
DOI: 10.1093/qjmed/hcaa278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the combinative use of acupotomy therapy and ultrasonic drug penetration in treating knee joint osteoarthritis

Abstract: Background Knee joint osteoarthritis is a chronic disease that affecting the health in aging population. Aim We explore a minimally invasive surgery combining the use of ultrasonic drug penetration to treat early stage of knee joint osteoarthritis. Design and Methods Total 75 patients were participated in acupotomy therapy and ultrasonic drug penetration to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A slow, progressive, and chronic disease, osteoarthritis is the leading cause of disability among elderly people. Existing studies showed that many cytokines, growth factors [ 22 ], and signaling pathways are involved in regulating osteoarthritis [ 23 , 24 ]. While NSAIDs can reduce the pain brought on by KOA, their long-term use may cause adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A slow, progressive, and chronic disease, osteoarthritis is the leading cause of disability among elderly people. Existing studies showed that many cytokines, growth factors [ 22 ], and signaling pathways are involved in regulating osteoarthritis [ 23 , 24 ]. While NSAIDs can reduce the pain brought on by KOA, their long-term use may cause adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, four auricular points on the side where KOA was present, corresponding to the knee and subcortical, adrenal, and endocrinal functioning received acupoint massage. The knee acupoints corresponded to pressure points that relieved knee pain, while the adrenal, subcortical, and endocrinal acupoints were linked to sedative and analgesic effects [ 24 ]. The knee and subcortical acupoints present in the ear are holographic targets for delivering therapy to the human body; when stimulated, the feedback information derived from these points is delivered immediately to the location of the disease to mobilize the meridians and stimulate the analgesic structures in the brain to release endorphins and enkephalin analgesic substances [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have shown that patients with knee osteoarthritis can have thinning of the cartilage layer and reduction of the cartilage in the early stage. Such signs can be detected by ultrasound, and there is a positive correlation between the degree of cartilage degeneration and the duration of knee osteoarthritis [18,19]. The results showed that the thickness of the femoral lateral malleolus cartilage and femoral medial malleolus cartilage in the study group was less than those in the control group, the depth of the suprapatellar capsule effusion and the thickness of the suprapatellar capsule synovium were greater than those in the control group (P < 0:05), and there was no significant difference between musculoskeletal ultrasound and arthroscopy in the detection rate of abnormal ultrasonic examination of knee osteoarthritis (P > 0:05), indicating that musculoskeletal ultrasound has high 3 Disease Markers diagnostic value in knee osteoarthritis and can detect the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages and dendritic cells release IL-23 during chronic inflammation. 4 , 57 , 58 The serum levels of IL-17a and IL-23 were increased in OA patients. 59 In PsA patients, a higher concentration of IL-23 and IL-17 triggered dactylitis and enthesitis.…”
Section: Inflammatory Responses In Oa Vs Psamentioning
confidence: 97%